Business Process Reengineering and Quality Performance in the Islamic Banks: The Information Technology as a Moderator - Mohd Rizal Razalli; Norlena Hasnan; Alminnourliza Noordin (International Journal of Supply Chain Management, 2017)
One of the critical challenges of business world is to manage change. This rapid rate of change has forced many companies to radically improve its business processes or better known as business process reengineering (BPR). Financial sector is one of the main drivers in economy in any nation and has been experiencing drastic change in its operations. This paper examines the effectiveness of business process reengineering (BPR) and the moderation role of information technology (IT) capability on the performance of Islamic bank in Malaysia. BPR dimensions namely change management, strategy alignment, management commitment, customer focus, IT investment, process redesign, adequate financial resource and less bureaucratic structure are investigated to observe their effects on the Islamic banks performance. The performance of Islamic bank is unique because it is based on three main quality aspects which include (1) educating individual, (2) public interest, and (3) establishing justice. However, in our case, the performance is measured by the cost spent by the banks to fulfill those three quality aspects. The direct relationship and moderation effects were analyzed using the Partial Least Square (PLS) structural equation modeling. Collectively, the results show the effect of BPR dimensions particularly change management and less bureaucratic sturucture on the performance of Islamic banks. The moderating effect of IT capability, however, is insignificant. The outcome of this study provides the important insights to both managers and researchers for further understanding of BPR factors particularly on the Islamic banks performance.